Ports vs. Roads: Infrastructure, Market Access and Regional Outcomes - Barthélémy Bonadio (CESifo GmbH, 2024)
What determines the relative gains from improving different parts of a transportation network? Ports and roads are key components of a country's infrastructure to access international markets. I provide a framework to jointly estimate the quality of different ports and trade costs on normal roads and expressways. I then build a general equilibrium model of international and internal trade with port and road infrastructure to assess the relative importance of ports versus roads in shaping international market access, and estimate it using a novel transaction-level export dataset for India. A key elasticity of route switching governs the relative gains from port vs road improvements. I find that returns of improving ports are higher than those for roads under the existing Indian infrastructure network, but improvements in ports and roads have different distributional implications.
Keywords: F10; R40; H54; 330; ports; infrastructure; market access; India